Comparative analysis of inflammatory markers as predictive markers for postoperative delirium in cardiac surgery patients: an observational study - Shan, Liang; Zheng, Keyang; Dai, Wenlong; Wang, Yintang; Hao, Peng (Frontiers in Medicine, 2025)
BackgroundPostoperative delirium (POD) is a common complication following cardiac surgery that significantly affects patient outcomes. Among inflammatory markers, the monocyte-to-lymphocyte ratio (MLR) has shown potential in predicting POD. However, studies on the relationship between neutrophil-to-lymphocyte ratio (NLR) or platelet-to-lymphocyte ratio (PLR) and POD are still lacking. Moreover, a direct comparison of the predictive capabilities of these three inflammatory markers (NLR, MLR, and PLR) for POD remains unexplored.MethodsThis observational study utilized the MIMIC database. We included 2,095 patients who underwent cardiac surgery. Multivariable logistic regression analysis, restricted cubic spline (RCS) analysis, and receiver operating characteristic (ROC) curve analysis were employed to assess the relationship between NLR, MLR, PLR, and POD.ResultsPOD occurred in 415 patients (19.8%). Multivariable logistic regression identified NLR (OR 1.05, 95% CI 1.03–1.08), MLR (OR 1.39, 95% CI 1.01–1.92), and PLR (OR 1.00, 95% CI 1.00–1.00) as independent risk factors for POD, all with P-values < 0.05. ROC curve analysis revealed NLR had the strongest predictive ability (AUC = 0.610, 95% CI: 0.589–0.631), outperforming MLR (AUC = 0.575, 95% CI: 0.553–0.596) and PLR (AUC = 0.553, 95% CI: 0.531–0.574). RCS analysis indicated linear or near-linear relationships between these markers and POD risk.ConclusionNLR, MLR, and PLR independently predicted postoperative delirium following cardiac surgery, with NLR demonstrating the strongest predictive capacity. These findings provided new tools for preoperative risk assessment and may improve postoperative management strategies for cardiac surgery patients.